CT Test: A Powerful Tool for Assessing Computational Thinking Skills in Biology - Ryan Ardiansyah; Dea Diella; Herni Yuniarti Suhendi; Novi Febrianti (FKIP UNIVERSITAS PAKUAN, 2024)
This research aims to create a tool for assessing students' computational thinking (CT) skills in relation to biology concepts. The study followed a research and development approach, utilizing a modified 4D design model, with the dissemination phase excluded. Various data collection techniques were employed, including observations, literature reviews, documentation, surveys, interviews, and tests. The findings showed that the developed instrument was valid, having been evaluated by three experts. The material expert rated it at 95%, the assessment and evaluation expert at 88%, and the linguist at 90%. In terms of readability, the instrument scored 75%, indicating a